(untitled) (Archives of Pediatrics of Uruguay, 2020)
Respiratory papillomatosis is an uncommon benign neoplasia caused by the Human Papilloma Virus, mainly by types 6 and 11. The typical symptoms of the larynx papillomatosis are dysphonia and stridor. For tracheobronchial papillomatosis, the symptoms are unspecific. This disease has an unpredictable clinical course and it tends to be recurrent. The objective of this paper is to describe one infrequent pediatric case, which initially showed unspecific symptomatology. Clinical case: six-year old child admitted due to a type 2 respiratory insufficiency. He had had clinical symptoms of progressive respiratory difficulty, stridor and snoring for two months. He developed acute high respiratory symptoms with intense functional respiratory and sleep tendency, and the initial check-up showed decompensated chronic respiratory acidosis with severe hypercapnia that required mechanical ventilation assistance. The respiratory function improved, but the suprasternal retraction, stridor and hypercapnia continued. The fibro laryngoscopy showed a supraglottic and a tracheal lesion with papilloma characteristics. Both were surgically resected and intralesional medical treatment with Bevacizumab and Acyclovir was administered. Samples for immunohistochemistry and pathology anatomy were taken, and the HPV type 11 was detected. Post-Surgical evolution was positive and after one month of follow-up the patient was asymptomatic and the control fibro laryngoscopy was normal. Conclusion: respiratory papillomatosis diagnosis and treatment is a challenge, due to its unspecific clinical manifestation and recurrent nature.